Legal aspects associated with the lack of possibilities of preventing the spread of toxocarosis and toxoplasmosis in Poland - Felsmann, Mariusz Z.; Felsmann, Mirosława (Translational Research in Veterinary Science, 2018)
The aim of the study is to examine the impact of changes in Polish law the possibility of interrupting the roads spread toxoplasmosis and toxocarosis. The authors’ assumption is to review the changes in Polish legal acts (acts and regulations) made in recent years in the context of combating toxocarosis and toxoplasmosis by the authorities of Polish government administration. An analysis was made of Polish laws regulating the control of zoonotic diseases (toxoplasmosis and toxocarosis), in particular acts which have been amended and changed in the last dozen or so years. The results of the analysis of changes in Polish law, relating to coping with toxocarosis and toxoplasmosis, clearly indicate the lack of legal grounds for effectively combating these diseases. The state public health services do not currently possess the legal means necessary to take effective action leading to the blocking of pathways along which these zoonoses spread. Currently the Polish law does not protect people against the possibility of contagion with toxoplasmosis and toxocarosis. The rights of animals, especially homeless cats, stand above the right of humans to protect themselves against parasites spread in public places by dogs and cats.